Pengemasan Paket Wisata di Desa Wisata Kampoeng Lama Kabupaten Deli Serdang - Hetty Claudia Nainggolan; Anita Rahayu (Manajemen dan Pariwisata, 2023)
The trend of sustainable tourism has become the government's attention in directing various regions to be able to move to accelerate the economy but still pay attention to the social and cultural aspects of the local community, one of which is by forming a tourist village. Kampoeng Lama Tourism Village is a tourist village located in Pantai Labu sub-district, Deli Serdang Regency, North Sumatra. Along with the development of tourist villages, in order to compete with other tourist villages, it is necessary to package tour packages as tourism products. Therefore, this study aims to create and produce tour packages based on activities that are already available in the Kampoeng Lama Tourism Village which is managed by the Kawan Lama Area. The method used by the author in this study is a descriptive method with a qualitative approach. Data collection techniques in this research are literature study, observation, documentation, and interviews. The result of this research is the creation of a tour package "The Authentic of Kampoeng Lama Village 2D/1N". Made based on the target market, students, families or groups. Itinerary for the Kampoeng Lama Tourism Village package designed by Kawan Lama Area matrix/table. While calculating the price of the package, Kawan Lama Area classified it into fixed cost and variable cost. It is hoped that Kawan Lama Area can cooperate with various stakeholders in marketing The Authentic of Kampoeng Lama Village 2D/1N tour package so that it can increase the economy in the Kampoeng Lama Tourism Village.